LDGM Codes for Channel Coding and Joint Source-Channel Coding of Correlated Sources - Javier Garcia-Frias; Wei Zhong (EURASIP Journal on Advances in Signal Processing, 2005)
We propose a coding scheme based on the use of systematic linear codes with low-density generator matrix (LDGM codes) for channel coding and joint source-channel coding of multiterminal correlated binary sources. In both cases, the structures of the LDGM encoder and decoder are shown, and a concatenated scheme aimed at reducing the error floor is proposed. Several decoding possibilities are investigated, compared, and evaluated. For different types of noisy channels and correlation models, the resulting performance is very close to the theoretical limits.